MOBILE HEALTH APPLICATIONS FOR YOUTH MENTAL HEALTH: A NARRATIVE REVIEW OF EVIDENCE, CHALLENGES, AND FUTURE DIRECTIONS - Yulduz Mansurova (Modern American Journals, 2025)
Mental health disorders among adolescents and young adults represent a growing global public health challenge. Mobile health (mHealth) applications have emerged as accessible and scalable tools for providing psychosocial support and self-help interventions. This narrative review synthesizes findings from recent systematic reviews and meta-analyses (2019–2025) on the effectiveness, engagement, safety, and methodological quality of mental health apps targeting depression, anxiety, and related conditions in youth. Evidence suggests small-to-moderate effects of app-based interventions in controlled trials, particularly when incorporating cognitive-behavioral therapy (CBT) and mindfulness-based strategies. However, engagement and retention remain major barriers, and evidence on long-term outcomes and adverse events is limited. Methodological shortcomings, such as small sample sizes and short follow-up periods, constrain generalizability. Future research should prioritize high-quality randomized trials, sustainable engagement strategies tailored to youth populations, and integration of digital interventions into clinical and educational systems with stronger regulatory oversight on content validation and data security.
Keywords: M Health, mobile applications, youth mental health, depression, anxiety, digital psychology.